Mechanical engineering for sustainable development - Rao, C. S. P., 1963- (Toronto ; [Hackensack?] New Jersey : Apple Academic Press, 2019)
This volume provides valuable insight into diverse topics related to mechanical engineering and presents state-of-the-art work on sustainable development being carried out throughout the world by budding researchers and scientists. Divided into three sections, the volume covers machine design, materials and manufacturing, and thermal engineering. It presents innovative research work on machine design that is of relevance to such varied fields as the automotive industry, agriculture, and human anatomy. The second section addresses materials characterization, an important tool in assessing proper materials for application-oriented jobs, and emerging unconventional machining processes that are important in design engineering for new products and tools. The section on thermal engineering broadly covers the use of viable alternate fuels, such as HHO, biodiesel, etc., with the objective of reducing the burden on petroleum reserves and the environment.
22: Optimization of Powder-Mixed Electric Discharge Machining Parameters Using Taguchi and Grey Relational Analysis Based on Material Removal Rate and Surface Roughness23: Geometry-Based Dynamic Behavior of Functionally Graded Material Under Fluctuating Loads; 24: A Cost and Energy-Effective Automatic Material Handling System for Small-Scale Industry; 25: A Survey on Application of a System Dynamic Approach in Supply Chain Performance Modeling; 26: Gel Casting of Si3N4-SiO2 Ceramic Composites and Evaluation Characteristics; PART III: Thermal Engineering (TE)
OCLC-licensed vendor bibliographic record.
Keywords: Mechanical engineering; Sustainable engineering; TECHNOLOGY & ENGINEERING / Mechanical; SCIENCE / Energy; TECHNOLOGY / Engineering / Mechanical